An evaluation of the impact of abattoir processing on the levels of Campylobacter spp. and Enterobacteriaceae on broiler carcasses - Papoula-Pereira, Rita; Abdulla, Khalid; Silver, Georgia; Kellett, Abigail; Antic, Dragan (Frontiers in Microbiology, 2025)
BackgroundTwenty years since the monitoring of foodborne diseases started in the EU and United Kingdom, Campylobacter infection is still the most reported zoonosis. One of the crucial reasons for this is thought to be an increase in Campylobacter virulent strains in the chicken meat as a consequence of insufficient and/or inadequate controls on farm and during chicken slaughter and processing. This study aimed to investigate the impact of abattoir processing on the levels of Campylobacter spp. and Enterobacteriaceae on broiler carcasses, including the effect of hot water carcass immersion and ultrasound intervention, the abattoir’s compliance with process hygiene criteria (PHC) and antimicrobial resistance in Campylobacter spp. strains.MethodsNeck skin samples (n = 270) were taken from seven broiler batches over seven sampling days in one abattoir, immediately after defeathering, evisceration, hot water immersion/ultrasound intervention and air-chilling (40 samples per day/batch). Quantification of Campylobacter spp. and Enterobacteriaceae was performed based on ISO methods following Campylobacter spp. confirmation on the MALDI-TOFF and PCR. Antimicrobial susceptibility testing of Campylobacter spp. was performed via disc diffusion method using EUCAST guidelines.ResultsCampylobacter jejuni was confirmed in 93.7%, C. coli in 1.1% and Campylobacter spp. in 1.9% of samples. Abattoir processing significantly reduced final carcass microbial load, with an overall reduction in Campylobacter and Enterobacteriaceae levels of 1.14 log10 and 1.43 log10, respectively. Hot water immersion and ultrasound intervention substantially decreased Campylobacter levels by 0.85 log10 and Enterobacteriaceae levels by 0.82 log10. The abattoir was found unsatisfactory regarding compliance with PHC for Campylobacter levels within the sampling window, but satisfactory when the new proposed PHC for Enterobacteriaceae levels was applied. Antimicrobial resistance was found in Campylobacter isolates from all seven chicken batches, and 48.7% of isolates showed resistance to at least one antibiotic. Most isolates exhibited resistance to tetracycline (45%), nalidixic acid (41%), and ciprofloxacin (39%). Multidrug resistance was found in 2.7% of Campylobacter isolates, with combined resistance to ciprofloxacin, erythromycin and tetracycline in 1.6% of isolates.ConclusionThis study confirmed significant reduction of microbial load on chicken carcasses during abattoir processing, with an emphasis on the importance of using interventions in meat industry. The prevalence of resistance to ciprofloxacin and tetracycline is not declining in Campylobacter spp. on chicken meat, despite antimicrobial stewardship initiatives, and the presence of multidrug resistant strains may be of public health concern.